Essays on microeconomic theory - Droege, J (2022)
In three distinct, yet interrelated essays I examine real-world phenomena at the intersection of microeconomic theory and behavioural economics. To do so, I modify longstanding concepts in information economics, including signalling and games of incomplete information, to include non-standard preferences, non-standard beliefs, and non-standard decision-making. As a result, I obtain novel theoretical predictions that provide insights for policy.